Breast Cancer: Getting through Chemotherapy...Tips from Survivors - Martha C. Monroe; Barbara F. Shea (EDIS)
FCS8832, a 3-page fact sheet by Martha C. Monroe and Barbara F. Shea, offers some tips from the Gainesville Breast Cancer Support Group to help cancer patients get through chemotherapy treatments. Published by the UF Department of Family Youth and Community Sciences, February 2010.